ANALISIS PENGEMBANGAN E-GOVERNMENT DI KABUPATEN KENDAL - Setiani, Yulinar Ayu; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
E-government is the use of information and communication technology to support government activities. In this context, the existence of e-government is needed to meet the demands of society to create clean, transparent government, and able to answer the demands of society quickly, accurately, effectively and efficiently. The e-Government development in Kendal District is a government program to increase transparency, accountability and public services. The low quality of e-government results in Kendal Regency is one of the main issues that will be solved by researchers using qualitative research methods, with emphasis on qualitative-verification design. The purpose of this study is to analyze the development of e-government and the factors inhibiting e-government in Kendal District. To find out how far the development of e-government in Kendal District in this study using the results of research and research from Hardvard JFK School of Government yaiu successful elements that include support, capacity, and value. The results of observations and interviews with some informants indicate that the development of e-government in Kendal Regency has been running well. The development of e-government in Kendal is also hampered by several factors such as human resources and infrastructure so that Kendal regency government needs to improve human resources and infrastructure infrastructure to support the success of e-government development in Kendal Regency.